2022
DOI: 10.1002/app.52462
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose and lignin as carbon black replacement in natural rubber

Abstract: Lignocellulosic fillers have gained attention as biofillers due to their low cost, availability, and eco‐friendly nature. Various lignocellulosic fillers from different sources having different chemical compositions have been used in natural rubber (NR) without sufficient comparison. So the objective of this study is to investigate the effect of two well defined industrial fillers (lignin and cellulose) along with black spruce cellulosic pulps obtained from an organosolv process on the properties of NR. To thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Furthermore, the addition of high lignin content decreases the tensile strength of rubber composites due to filler agglomerations. [ 14–19 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the addition of high lignin content decreases the tensile strength of rubber composites due to filler agglomerations. [ 14–19 ]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of high lignin content decreases the tensile strength of rubber composites due to filler agglomerations. [14][15][16][17][18][19] Cellulose nanocrystals (CNC) is another filler usually prepared by acid hydrolysis of lignocellulosic fibers with H 2 SO 4 . After acid hydrolysis, SO 3 À functional groups are introduced onto the CNC surface helping its dispersion in water through electrostatic repulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Kazemi et al [106] compared cellulose and lignin to replace CB in NR composites. The results showed that the lignin/NR composites exhibited longer curing time than the composites filled with cellulose.…”
Section: Lignin/nr Compositesmentioning
confidence: 99%
“…Hybrid systems containing lignin and conventional fillers are attracting considerable attention for rubber composites [106,111]. Yu et al [111] showed that replacing silica with lignin decreased the Payne effect and improved processability, as well as increased the curing time and elongation at break.…”
Section: Lignin/nr Composites Reinforced With Hybrid Fillersmentioning
confidence: 99%
“…In the rubber industry, the utilization of natural fillers from natural resources is very beneficial as it lowers the costs of production as cheaper materials (natural fillers) are used [ 11 ]. Natural fillers are known to be environmentally friendly, fully degradable, sustainable, available in abundance, cheap, and low in density [ 9 , 13 , 14 ]. In the last few years, sustainable materials derived from plants, such as cellulose nanocrystals, natural fibers, lignin, and biochar are widely incorporated in various studies as a replacement or complementary fillers for rubber composites [ 8 ].…”
Section: Introductionmentioning
confidence: 99%